2018
DOI: 10.1016/j.jpain.2017.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Daily Fluctuations of Progesterone and Testosterone Are Associated With Fibromyalgia Pain Severity

Abstract: Sex hormones fluctuate normally in women with fibromyalgia, but may still contribute to pain severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 48 publications
4
30
1
Order By: Relevance
“…It is important that these findings are replicated in women with chronic pain before starting to consider whether there may be any therapeutic benefit of inducing a high estradiol/high progesterone state. However, a recent study demonstrating a negative relationship between daily progesterone levels and pain ratings in women with fibromyalgia is in line with our findings ( 70 ).…”
Section: Discussionsupporting
confidence: 93%
“…It is important that these findings are replicated in women with chronic pain before starting to consider whether there may be any therapeutic benefit of inducing a high estradiol/high progesterone state. However, a recent study demonstrating a negative relationship between daily progesterone levels and pain ratings in women with fibromyalgia is in line with our findings ( 70 ).…”
Section: Discussionsupporting
confidence: 93%
“… 47 Estradiol may be pronociceptive, 48 whereas studies have generally shown that testosterone and progesterone may play a protective role in pain severity. 49 Another theoretical mechanism is that serotonin is a neurotransmitter involved in the modulation of pain and is found is significantly higher proportions in males. 21 , 50 However, to date, the biochemical role of sex hormones and neurotransmitters in hyperalgesia of FM appears to be limited, 51 and these explanations remain speculative with no definitive evidence.…”
Section: Discussionmentioning
confidence: 99%
“…There are clinical studies showing that testosterone replacement therapy reduces pain outcomes and improves the quality of life of patients with hypogonadism (Aloisi et al, 2011 ), thereby supporting the hypothesis that testosterone may have an anti-nociceptive role. However, some studies suggest that testosterone is necessary for a small nociceptive response (Thompson et al, 2008 ; Glaser et al, 2012 ; Schertzinger et al, 2017 ). According to these studies, low levels of testosterone are related to high discomfort, anxiety, and pain in response to noxious hot stimuli (Choi et al, 2017 ).…”
Section: Trpv1 Trpm8 and Testosteronementioning
confidence: 99%